1994
DOI: 10.1111/j.1748-1716.1994.tb09662.x
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of secretory granules from the feline parotid gland: action of NANC transmitters per se

Abstract: A parotid acinar degranulation of approximately 60 and 40% was observed in cats under pentobarbitone anaesthesia after a 90-min period of continuous stimulation of the parasympathetic auriculo-temporal nerve at 10 Hz in the absence and presence of atropine, respectively. Atropine completely abolished the large fluid response of the gland to the nerve stimulation. In the non-atropinized cats, bethanechol, infused into the carotid artery at a dose rate evoking a salivary flow similar to that in response to paras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…The appearance of the peptide‐stimulated mucous cells was similar to that in response to carbachol, also previously described in the human submandibular gland (Riva et al , ). Thus, humans belong to those species (rat, cat, dog, ferret, pig, sheep, mink and calf) in which VIP causes the acinar cells of salivary glands to lose secretory granules and to release proteins/glycoproteins, and when administered in vivo , during ongoing secretion, causes the flow rate to accelerate and the salivary protein concentration to increase (Lundberg et al , ; Inoue and Kanno, ; Reid and Heywood, ; Reid and Titchen, ; Bobyock and Chernick, ; Ekström and Tobin, , ; Tobin et al , ; Turner and Camden, ; Ekström et al , ; Culp and Richardson, ; Calvert et al , ; Ekström and Ekström, , ). So far, the rat and the mink are the only species where VIP per se , in addition, has been found to evoke an overt flow of saliva (Ekström et al , ; Tobin and Ekström, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The appearance of the peptide‐stimulated mucous cells was similar to that in response to carbachol, also previously described in the human submandibular gland (Riva et al , ). Thus, humans belong to those species (rat, cat, dog, ferret, pig, sheep, mink and calf) in which VIP causes the acinar cells of salivary glands to lose secretory granules and to release proteins/glycoproteins, and when administered in vivo , during ongoing secretion, causes the flow rate to accelerate and the salivary protein concentration to increase (Lundberg et al , ; Inoue and Kanno, ; Reid and Heywood, ; Reid and Titchen, ; Bobyock and Chernick, ; Ekström and Tobin, , ; Tobin et al , ; Turner and Camden, ; Ekström et al , ; Culp and Richardson, ; Calvert et al , ; Ekström and Ekström, , ). So far, the rat and the mink are the only species where VIP per se , in addition, has been found to evoke an overt flow of saliva (Ekström et al , ; Tobin and Ekström, ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to VIP, the secretory effect of SP (and its related non‐mammalian tachykinin physalaemin) appears to be limited to a few species, where the output of proteins is accompanied by a lively flow of saliva. The release of proteins in response to VIP and SP is morphologically reflected by the loss of storage granules from the acinar cells (Ekström et al , ; Ekström and Ekström, , ; Del Fiacco et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that the flow rate was produced by vasoactive intestinal peptide (VIP) release (25), however this seems unlikely since VIP receptor activation is linked to an increase in cAMP, not [Ca 2ϩ ] i . Indeed, Ekstrom et al (26) reported that VIP treatment caused little to no fluid secretion in feline parotid glands. Interestingly, the electrically evoked "atropine-resistant" fluid secretion was ϳ30% of the response prior to muscarinic receptor inhibition in the ferret submandibular gland (3).…”
Section: Discussionmentioning
confidence: 99%
“…However, the significant (P < 0.05) difference between non-atropinized and atropinized rats subjected to the long-term period of stimulation may nevertheless indicate some loss of granules in the non-atropinized animals during the last 40 min. The observation that the rate of depletion of the parotid gland content of some neuropeptides, including substance P and VIP, in response to stimulation of the parasympathetic innervation is lower in the absence of atropine than in its presence (Tobin et al 1994) may be important in this connection. Positive interactions between agonists may also be important.…”
Section: Discussionmentioning
confidence: 99%
“…In the rat, exogenous VIP evokes a small flow of parotid saliva (Ekstrom, Mansson & Tobin, 1983), very rich in protein and, in the feline parotid gland, VIP has been shown to release acinar secretory granules (Ekstrom, Asztely, Helander & Tobin, 1994). Concomitantly with the decrease in the glandular content of VIP, there is also a marked decrease in the content of parasympathetic postganglionic substance P. In the rat, substance P evokes a large flow of parotid saliva with a low concentration of protein (Ekstrom & Wahlestedt, 1982;Ekstrom et al 1983;Ekstrom & Olgart, 1986).…”
Section: Discussionmentioning
confidence: 99%